Bibliographical resources for international studies in political communication: analyzing focus and methods - Hánninen, Liisa Irene (Documentación de las Ciencias de la Información, 2012)
During the last decades, political communication has been of great interest not only to communication researchers, but also to scholars of political science and political marketers. Furthermore, we can find references in books and research papers dedicated to sociology, social psychology and consumer behavior. As a part of a larger study of Madrid Community and City elections in 2011, ESAVICOM research group from the Complutense University of Madrid mapped some of the most interesting bibliographical resources in order to analyze the diverse focus and methods used in international studies. The main resources found and their conclusions are exposed in the present paper, explaining in parallel how political communication can be approached from different points of view: media discourse and effects, communication strategies, effects of interactive media and lately, also from feminist advocacy.
Keywords: Political communication; bibliographical resources; scientific magazines; multidisciplinary study; international focus